Internal organization and performances of saving and loan associations: Evidence from rural Tanzania - Pamuk, Haki; Asseldonk, Marcel van; Tumainiely, Kuweka; Ruben, Ruerd; Wattel, Cor (2020)
Subsistence farmers in rural areas of developing countries are usually outside the current reach of banks and formal microfinance institutions. They do not have access to savings accounts, insurance products, and agricultural credit facilities, limiting those farmers’ investment in agriculture. Being at the outreach of those institutions, those farmers established, so-called savings and loan associations, self-managed groups of 20-30 individuals meeting regularly to provide its members a safe place to save and obtain emergency aid and small loans. When efficiently organized, those associations may provide a secure platform to save and access loans to invest in climate-smart agriculture and mitigate income shocks. The objective of this study is to identify the role of the associations in financing agriculture, major bottlenecks and organizational characteristics that might explain their financial performances. We use survey data from 48 savings and loan associations in rural Tanzania with members trained for adopting climate-smart agricultural practices. We identify that 45% of the loans of associations are distributed for agricultural investment purposes and the major bottleneck is to low savings and participation rates, and late repayment or defaults of loans. We find that the size of associations and record-keeping matters. The average amount of loan received per member approximately doubled for associations with twice as many members, and default rates decrease with the accurate financial recording practices. Our findings suggest that savings and loan associations could strengthen the financial resilience of its members by empowering their members through financial record keeping training. At the same time, they can add new members to the associations.